20 år med fysikkprestasjoner i fritt fall - Hole, Arne (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"The book discusses various challenges and solutions related to the coordination of health and welfare services. Coordination is central to creating integrated services for users with complex needs. In order to understand the challenges and opportunities associated with creating such services, one needs knowledge related to organizations and the organizational context. The book's chapters takes on an organizational perspective where patterns and explanations are sought in formal and informal structures, processes and culture.